A Virtual Ethnography Study: The Role of Cultural Radios in Campursari Music Proliferation in East Java - Zainal Abidin Achmad (Hasanuddin University, 2020)
Campursari music is a trend on the radio and a favorite of the people of East Java, so it is shifting towards popular culture. This study aims to uncover the proliferation of campursari music and the role of cultural radios. This qualitative research uses a virtual ethnography method, which focuses on the physical presence and virtual text together. The subjects are technology (radio and communication technology on the internet), humans (radio listeners), physical interactions, and virtual interactions. Data collection used participant observation through observation and interviews offline and online in the form of various texts, writings, images, and audiovisuals on Facebook, Twitter, WhatsApp, Instagram, and Youtube. The informants of this study were four cultural experts, namely: Sumadi, Anton Sani, Ibnu Hajar, and Juwono. This study carried out participatory involvement for one year in the virtual world and 30 days living in four cities: Surabaya, Nganjuk, Banyuwangi, and Sumenep.